Factors associated with insomnia in health professionals of a public hospital in Trujillo, Peru - Caballero-Alvarado, José (2020)
Objective: To identify the factors associated with insomnia in health professionals of a public hospital in Trujillo, Peru. Materials and methods: The Athens Insomnia Scale (AIS) was administered to 220 health professionals. The chi-square test and Student's t-test were used. In addition, the multivariate analysis was performed to identify the variables associated with insomnia. Results: It was demonstrated that there is less risk of insomnia in professionals under 38 years of age (OR 0.77; 95 % CI 0.68 – 0.87; p < 0.05). There is more risk of insomnia in cases of work overload (OR 4; 95 % CI 1.22 – 9.73; p < 0.05),night shifts (OR 3.12; 95 % CI 1.01 – 9.73; p < 0.05), job tenure of more than 7 years in the hospital (OR 1.50; 95 % CI 1.22 – 1.85; p < 0.001) and low back pain (OR 11.28; 95 % CI 3.61 – 35.28; p < 0.05), the latter being the variable with the highest association value. Conclusions: Our study suggests that health professionals older than 38 years of age, with low back pain, under work overload, who work night shifts and with a job tenure of more than 7 years in the hospital are more at risk of suffering insomnia.